Proclivity to genocide : northern Nigeria ethno-religious conflict, 1966-present - Okoye, Grace O. (Lexington Books, 2014)
This book explores the ethnic and religious dimensions of the northern Nigeria ethno-religious conflict and develops a Genocide Proclivity Model for identifying the conflict's genocidal inclinations. It argues that proclivity to genocide, though currently latent, underlies most cases of the wanton killings in northern Nigeria.